P2X4 Forms Functional ATP-activated Cation Channels on Lysosomal Membranes Regulated by Luminal pH - Huang, Peng (American Society for Biochemistry and Molecular Biology, 2014)
P2X receptors are commonly known as plasma membrane cation channels involved in a wide variety of cell functions. The properties of these channels have been extensively studied on the plasma membrane. However, studies in amoeba suggest that P2X receptors are also present intracellularly and involved in vesicle fusion with the plasma membrane. Recently, it was shown that in addition to plasma membrane expression, mammalian P2X4 was also localized intracellularly in lysosomes. However, it was not clear whether the lysosomal P2X4 receptors function as channels and how they are activated and regulated. In this paper, we show that both P2X4 and its natural ligand, ATP, are enriched in lysosomes of COS1 and HEK293 cells. By directly recording membrane currents from enlarged lysosomal vacuoles, we demonstrated that lysosomal P2X4 formed channels activated by ATP from the luminal side in a pH-dependent manner. While the acidic pH at the luminal side inhibited P2X4 activity, increasing the luminal pH in the presence of ATP caused P2X4 activation. We further showed that, as for the plasma membrane P2X4, the lysosomal P2X4 was potentiated by ivermectin but insensitive to suramin and PPADS, and it permeated the large cation N-methyl-d-glucamine upon activation. Our data suggest that P2X4 forms functional ATP-activated cation channels on lysosomal membranes regulated by luminal pH. Together with the reported fusion effect of intracellular P2X in lower organisms, we speculate that the lysosome-localized P2X4 may play specific roles in membrane trafficking of acidic organelles in mammalian cells.